The Duplex Interaction of Microbiome with Chemoradiation and Immunotherapy: Potential Implications for Colorectal Cancer - Saeed, Azhar (Curr Colorectal Cancer Rep, 2019)
PURPOSE OF REVIEW: Gut microbiota has the ability to modify the metabolism of wide array of therapeutic drugs. Current treatment modalities used in colorectal cancer have a narrow therapeutic index with a side effects profile that decreases tolerance to these treatments and adversely affects treatment outcome. Harnessing the gut microbiota ability to modify oncotherapeutic drugs metabolism and hence efficacy, could be potentially used to improve treatment outcomes in colorectal cancer patients. This review will shed lights on important findings from recent microbiome interaction studies which would hopefully serve as a useful tool to guide future translative colorectal cancer research. RECENT FINDINGS: Recent advances in microbiome studies have revealed an interesting aspect of gut microbes carcinogenic properties in dysbiotic gut environment. Microbiota niche in colorectal cancer can also modify efficacy and toxicity profile of different oncotherapeutic treatment modalities from chemoradiotherapy to immunotherapy. Conversely, each of these treatment modalities has numerous effects on the gastrointestinal flora, causing changes in the gut microbial community that affects host morbidity and mortality. SUMMARY: Symbiotic gut microbiota is an incredible functioning organ that maintains essential aspects of our homeostasis and immunity. According to the recent body of literature, they also can modify efficacy of many therapeutic drugs including oncotherapy. Considering that unexplainable variable treatment outcomes as well as variable tolerance to treatment have been observed in colorectal cancer patients, studying gut microbiota modulatory effects on oncotherapy might be a feasible approach to explain this phenomenon.